Frequency of Radial Artery Occlusion in Patients Undergoing PCI Through Radial Approach at a Tertiary Care Teaching Hospital in Lahore - Zia , Sheikh Muhammad Rehman; Maken, Brig Ghulam Rasool; Khurana, Naresh Kumar; Noukhaiz , Namra; Asghar , Omar; Munir, Summaira (Indus Journal of Bioscience Research, 2025)
Introduction: Percutaneous Coronary Intervention (PCI), also known as coronary angioplasty or balloon angioplasty, is a minimally invasive procedure used to treat coronary artery disease (CAD). Objective: To determine the frequency of radial artery occlusion (RAO) in patients undergoing percutaneous coronary intervention (PCI) through radial approach. Methodology: This cross-sectional was conducted at Army Cardiac Hospital, Lahore from 1st August to 31st Jan. A non-probability consecutive sampling method was employed to select participants for the study. The PCI procedures were performed by a consultant radiologist, and the duration of the procedure was recorded. After 24 hours, a consultant cardiologist assessed the patients for the presence of RAO. If RAO was detected, appropriate therapy was provided based on the cardiologist’s recommendations. Results: Data were collected from 145 patients, with a mean age of 58.3 ± 9.7 years, ranging from 18 to 75 years. Among the participants, 58.6% were male and 41.4% were female. The average body mass index (BMI) was 28.4 ± 4.2 kg/m². In terms of smoking status, 34.5% were smokers, while 65.5% were non-smokers. Regarding diabetes status, 27.6% of patients had diabetes, while 72.4% were non-diabetic. These demographic characteristics provide a comprehensive overview of the study population. Out of the 145 patients included in the study, 6 (4.1%) developed radial artery occlusion (RAO) within 24 hours following the PCI procedure. The remaining 139 patients (95.9%) did not experience RAO. This result suggests a relatively low incidence of RAO among patients undergoing PCI via the radial approach in the study population.